TRADISI PERAYAAN IMLEK PADA MASYARAKAT ETNIS TIONGHOA DI KOTA MANADO - Kezia Joicelinda Wauran; Maryam Lamadirisi; Zoni Henki Singal (Labor Program Studi Pendidikan Sosiologi, 2020)
The research objective was to find out and describe the traditions of the Chinese New Year celebrations in the Chinese ethnic community in Manado City and the meanings contained in these traditions. The problem in the research is that Chinese New Year celebrations are often just a celebration and not a few ethnic Chinese communities in the city of Manado just carry on without understanding the meaning behind the tradition of Chinese New Year celebrations that have been inherited from her generations. This research uses qualitative methods with techniques such as observation and interviews. Unstructured interviews are independent interviews where the researcher does not use interview guidelines that have been arranged systematically and completely for data collection Sugiyono (2011: 233). The results of research in the field show that behind the traditions of Chinese New Year celebrations carried out by the Chinese ethnic community there are meanings contained in these traditions both from a cultural and religious perspective.